Creating a Strain Relief Loop during S1 Transforaminal Lead Placement for Dorsal Root Ganglion Stimulation for Foot Pain: A Technical Note. Issue 4 (6th December 2017) - van Velsen, Valery; van Helmond, Noud; Chapman, Kenneth B.
Abstract: Chronic neuropathic pain is often refractory to conventional medical treatments and leads to significant disability and socio‐economic burden. Dorsal root ganglion (DRG) stimulation has recently emerged as a treatment for persistent neuropathic pain, but creating a strain relief loop at the S1 level has thus far been a challenging technical component of DRG lead placement. We describe a refined technique for strain relief loop formation at the S1 level using a transforaminal approach that we employed in a 45‐year‐old patient with intractable foot pain. We successfully placed a strain relief loop in the sacral space in a predictable and easily reproducible manner using a transforaminal anchorless approach. The patient experienced a decrease in visual analog pain score (85%), and improvement in function during the trial period, and proceeded with permanent implantation. The described sacral transforaminal strain relief loop formation technique appears to be a more reliable and predictable technique of DRG lead placement in the sacrum than those previously documented.